Basal Stimulation as Developmental Support in At-Risk Newborns: A Literature Review - Petra Potmesilova; Milon Potmesil; Jana Mareckova (MDPI AG, 2023)
Background: The aim of this review of the literature was to find and summarize relevant research evidence available within the scientific sources and gray literature in accordance with the JBI recommendations. Search question: What effect does Basal Stimulation have on the cognitive-behavioral functions or temperament of a preterm or disabled infant? Methods: The following sources were searched: PSYCINFO, MEDLINE, PsycArticles, ERIC, Wiley Online Library, ProQuest Scopus, WOS, JSTOR, Google Scholar, and MedNar. The study contains an analysis of texts that have been published in the English, Czech, and German languages. The search time span was set at 15 years. Results: A total of 15 sources were found for the specified topic. Conclusions: In all cases, there was confirmation about the positive influence of the concept of "Basal Stimulation" on the cognitive-behavioral functions and temperament of premature and disabled children.